A Primer on Employment and Intellectual Property Law: Legal Guidance for Supervisors of Assessment and Institutional Research Staff. Issue 172 (9th June 2017) - Knight, William; Lugg, Elizabeth Timmerman
Abstract : Institutional research (IR) leaders rely on staff members to accomplish office missions and support institutional decisions. Like any supervisors in higher education, IR leaders must be familiar with a host of employment and intellectual property laws that guide the institution/employee relationship. This chapter offers insights into specific issues IR supervisors and staff members should heed.